Practice, Experiences, and Facilitators of Simulation-Based Training During One Year of Implementation in 30 Hospitals in Tanzania - Benjamin A. Kamala MD, PhD; Robert Moshiro MD, PhD; Florence S. Kalabamu MD, MMED; Torgeirsen Kjetil BScN, MSc; Godfrey Guga BSc; Beatrice Githiri BSc; Justine Samson BSc; Philimon Chavala BScN; Grace Qorro MD, MPH; Damas Kayera MD, MPH; Ivony Kamala BScN, MPH; Catherine Massay BScN, MSc; et al. (SAGE Open Nursing)
Introduction Enhancing the proficiency of healthcare workers (HCWs) in handling birth-related complications is crucial for reducing maternal and newborn morbidity and mortality. To achieve this, the Safer Births Bundle of Care offers a comprehensive set of innovative, simulation-based training interventions designed to strengthen the skills and competencies of HCWs working as skilled birth attendants. Objective To describe the use of in-situ low-dose, high-frequency simulation-based training, and the experiences of this usage among HCWs and stakeholders at facilities in Tanzania. Methods This mixed-methods study included quantitative and qualitative data collected between July 2021 and July 2022 across 30 health facilities in five regions of Tanzania. NeoNatalie Live (NNL) simulators were installed for independent skills and scenario training, and in-situ facilitator-led team simulations were introduced. The training frequency was analyzed using descriptive and analytical statistics, and mentorship and supervision reports were analyzed using qualitative content analysis. Results A large and sustained number of in-situ NNL skill-training sessions ( n  = 35,101) and facilitator-led team simulations ( n  = 266) were conducted during the first year. Clinical burden per HCW did not affect the frequency of NNL skills training at the health facility level ( r  = −0.16, p  = .40) nor facilitator-led team simulations. There was a positive but weak correlation between the frequency of facilitator-led team simulations and NNL skills training ( r  = 0.34, p  = .05). Qualitative data showed a high degree of motivation and participation among all stakeholders, and active use of hospital data, both clinical indicators and training data, was perceived as a success factor. Conclusion Facilitator-led in-situ simulation training was more likely to occur where individual skills-training sessions were recorded. Training sessions took place regardless of the increased workload.